THE EVALUATION OF THE INTERNAL APPLICATION SYSTEM OF CASH EXPENSES CONTROL IN DRINKING WATER COMPANY - Hendra Railis; Eko Cahyo Mayndarto; Rudi Ginting; Surachman Surachman (Yayasan Education and Social Center, 2022)
Accounting, in general, is a system of producing financial information used by users in the business decision-making process. Cash is an object that is often poorly represented because cash is the most valuable of all assets and can be transferred quickly, and everyone needs it. This study aims to determine the effect of the internal control system on cash receipts at drinking water companies. This study uses a qualitative approach. The data is collected through interviews and documentation. The results showed the evaluation of the implementation of the internal control system on cash disbursements in the company. The internal cash control system for cash sales is sufficient for several functions, namely capacity functions, cash functions, accounting features, and the documents used, namely the sales function, cash function, and accounting function. The records used are cash income and inventory cards, internal controls, daily accounting records with accounting features, and cash functions to compare cash balances according to records with their sales. Physical cash, so they happen the same between the two